Association Analysis for Morpho-Physiological and Yield-Attributing Traits in Foxtail Millet (Setaria italica L. Beauv.) - B. Harsha Vardhan; Ragimekula, Narasimhulu; M. Shanthi Priya; A. Chandra Sekhar (Annals of Arid Zone, 2025)
In winter (rabi) 2023–2024, at the Regional Agricultural Research Station, Nandyal, research on trait association and path analysis were carried out with an emphasis on 16 morpho-physiological and yield-attributing traits among 50 foxtail millet germplasm accessions. The results revealed that the majority of genotypic correlation coefficient estimations were higher than corresponding phenotypic correlations indicating the strong inherent associations among the traits. The yield-attributing traits viz., fodder yield plant-1, harvest index, plant height, panicle length, flag leaf length at flowering, 1000 grain weight, days to 50% flowering and flag leaf width at flowering had a significant and positive association with grain yield plant-1, whereas abortive grain rate and number of productive tillers had displayed negative association. Grain yield plant-1 was found to be significant and positively associated with physiological traits such as photosynthetic rate, stomatal conductance, transpiration rate, and relative water content, suggesting strong source and sink relationship. The strong and favorable direct impacts of fodder yield plant-1, harvest index, days to 50% flowering, flag leaf length and width at flowering, photosynthetic rate, relative water content, abortive grain rate and 1000 grain weight on grain yield plant-1 were found in the genotypic and phenotypic path analysis. Based on trait association and path analysis, the most important yield-attributing traits were the fodder yield plant-1, harvest index, flag leaf length and width, photosynthetic rate, relative water content and the 1000-grain weight. Therefore, these attributes should be given top priority when formulating the selection criteria for the foxtail millet grain yield improvement programme